Altruism and Time Consistency: The Economics of Fait Accompli - Lindbeck, Assar; Weibull, Jörgen W. (Journal of Political Economy, 1988)
This paper analyzes the strategic and intertemporal interaction between two economic agents who have "overlapping" concerns, such as altruistic concerns for each other's welfare. The agents may be two individuals, a social bureau and a client, or two units in an organization. The authors show how the presence of such common concerns may lead to socially inefficient outcomes, in which one economic agent "free rides" on the other's concerns. They also brief ly discuss how this inefficiency and free riding, in the context of interaction between individuals, might be mitigated by compulsory social security systems. As another example, the authors interpret th e inefficiency in terms of Janos Kornai's "soft budget constraints" within organizations. Copyright 1988 by University of Chicago Press.